Turbulence at the Top: A New Perspective on Governance Structure Changes and Strategic Change - Goodstein, Jerry; Boeker, Warren (Academy of Management Journal, 1991)
Organizational theorists have traditionally focused attention on the relationship between chief executive officer (CEO) succession and strategic change. This study extends that perspective and explores the effects of changes in an organization's management, ownership, and board of directors on the process of strategic change. The results of this research suggest that changes in ownership and board have significant independent and interactive effects on strategic change.